Miro sculpts mitochondrial dynamics in neuronal health and disease - Devine, Michael J.; Birsa, Nicol; Kittler, Josef T. (Neurobiology of disease, 2016)
Neurons are highly polarised cells with an elaborate and diverse cytoarchitecture. But this complex architecture presents a major problem: how to appropriately distribute metabolic resources where they are most needed within the cell. The solution comes in the form of mitochondria: highly dynamic organelles subject to a repertoire of trafficking, fission/fusion and quality control systems which work in concert to orchestrate a precisely distributed and healthy mitochondrial network. Mitochondria are critical for maintaining local energy supply and buffering Ca2+ flux within neurons, and are increasingly recognised as being essential for healthy neuronal function. Mitochondrial movements are facilitated by their coupling to microtubule-based transport via kinesin and dynein motors. Adaptor proteins are required for this coupling and the mitochondrial Rho GTPases Miro1 and Miro2 are core components of this machinery. Both Miros have Ca2+-sensing and GTPase domains, and are therefore ideally suited to coordinating mitochondrial dynamics with intracellular signalling pathways and local energy turnover. In this review, we focus on Miro's role in mediating mitochondrial transport in neurons, and the relevance of these mechanisms to neuronal health and disease.